Distributed routing algorithm with dynamic connection partition for mobile ad hoc networks. Issue 4 (1st July 2019) - Wang, Nan; Zhao, Hai; Hai, Long
Abstract : Mobile ad hoc networks (MANETs) are attractive for many applications because of their easy‐to‐use and self‐organising nature. However, the routing overhead problem has always been a bottleneck restricting the development of MANETs technology. The reason behind is the traditional blind flooding methods and frequent route initiations caused by node mobility. Reducing routing overhead has a huge impact on saving energy consumption of mobile nodes and improving the MANETs performance. In this study, a distributed dynamic routing algorithm is proposed to establish an efficient routing mechanism for MANETs. Based on the mobility of nodes, a fuzzy positional relationship between nodes is constructed. Using this relationship, an improved routing method is designed. The authors characterise this relationship between nodes and implement the proposed algorithm in an ad hoc routing architecture. The simulation results show that the proposed routing algorithm achieves good performance in reducing routing overhead and improves the efficiency of packet transmissions in MANETs.